VALUES OF BEING ANALYSIS IN R.J. PALACIOâ€™S NOVEL â€œWONDERâ€ - Safnidar Siahaan, Safnidar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
The purposes of this research are to find out the values of being described in R.J Palacioâ€™s novel based on Lindaâ€™s Theory of Values. This research design was qualitative research. The data collected based on the characters in the novel, such as: action, dialogues, thoughts, appearances, and reaction to other character which revealed in the novel. The result showed that the educational values in the novel especially on the value of being, those are: honesty, courage, peace and self-reliance and potential.